Political rules of the road Representatives, Senators, and Presidents share their rules for success in Congress, politics, and life (The Rowman & Littlefield Publishing Group, 2009)
Political Rules of the Road is a collection of informal rules that members of Congress have used to guide their political careers and private lives. Our current and former representatives, senators, governors, cabinet officials, and presidents have valuable advice to offer about how to be successful in Congress, politics, and life. At the request of Lou Frey, 172 political leaders contributed over 500 rules that cover a wide variety of topics: campaigns and elections, congressional service, representation and decision making, political parties and partisanship, media and ethics, politics, policy and life. These rules and anecdotes shed light on how Congress really works and provide a roadmap for how to be successful in politics and in life.